«Failed State» and «Gray Areas» of World Politics:the Present Generation or Past - Elizaveta A. Pakhomova (Сибирское юридическое обозрение, 2017)
The article describes the criteria for ideas “failed state” and a “gray zone” of world politics. On the basis of States' implementation of the internal functions of the conclusion of the similarity of the past with the modern states and failed state “gray zones” of world politics. Identified three types of failed state in the modern world.